2016
DOI: 10.1038/srep24728
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of lncRNA-ATB suppresses autocrine secretion of TGF-β2 by targeting ZNF217 via miR-200c in keloid fibroblasts

Abstract: Abnormally high activation of transforming growth factor-β (TGF-β) signaling has been demonstrated to be involved in the initiation and progression of keloids. However, the functional role of long non-coding RNA (lncRNA)-activated by TGF-β (lncRNA-ATB) in keloids has not been documented. Here we investigated the role of lncRNA-ATB in the autocrine secretion of TGF-β in keloid fibroblasts (KFs) and explored the underlying molecular mechanism. Using immunohistochemistry and quantitative RT-PCR analysis, we showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 36 publications
1
66
0
Order By: Relevance
“…Deregulated methylation status at the ZNF217 gene promoter has been observed in glioblastoma and breast cancer. LncRNA-ATB also regulates ZNF217 expression via miR-200c in keloid fibroblasts and breast cancer [44, 45]. In the current study, we found two functional binding sites of MAZ within the promoter of ZNF217 by ChIP assay and luciferase assay.…”
Section: Discussionsupporting
confidence: 60%
“…Deregulated methylation status at the ZNF217 gene promoter has been observed in glioblastoma and breast cancer. LncRNA-ATB also regulates ZNF217 expression via miR-200c in keloid fibroblasts and breast cancer [44, 45]. In the current study, we found two functional binding sites of MAZ within the promoter of ZNF217 by ChIP assay and luciferase assay.…”
Section: Discussionsupporting
confidence: 60%
“…miRs are small endogenous noncoding RNAs (21‐24 nucleotides) that act as critical roles in numerous biological processes . Accumulating evidence has identified that several lncRNAs function through regulating expression of miRs, including lncRNA‐ATB . miR‐195, located at chromosome 17, has been reported to repress angiogenesis in breast cancer .…”
Section: Discussionmentioning
confidence: 99%
“…The proliferation of hypertrophic scar fibroblasts was reported to be affected by the non-coding RNAs miR-200b, miR-21 and miR-143-3p [27][28][29]. The functional interactions of lncRNAs, miRNAs and mRNAs could lead to a new explanation for the pathogenesis of keloids [8]. We used DIANA-LncBase v2 (www.microrna.gr/LncBase) [30], LNCipedia v4.0 (www.lncipedia.org) [31] and NPInter v3.0 (www.bioinfo.org/NPInter/) [32] to determine whether any miRNAs could associate with lncRNA8975-1.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that lncRNAs play important roles in keloid formation [8], scleroderma [9], lung fibrosis [10], and other fibrotic disorders [11] by acting through diverse mechanisms. Recently, our group discovered that lncRNA8975-1 (TCONS_00013888 in UCSC hg38; also named NONHSAT122029 in NONCODEv4), an lncRNA located upstream of the COL1A2 gene on chromosome 7 (UCSC hg38, chr7:94278999-94392179, ChIPBase named it lncRNA8975-1), was overexpressed in regressive scars compared to mature scar tissues [12].…”
Section: Introductionmentioning
confidence: 99%